2023
DOI: 10.1108/bpmj-07-2023-0551
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the effects of value creation, intellectual property and organizational creativity on artificial intelligence focused enterprises

Fatih Pinarbasi,
Fatma Sonmez Cakir,
Duygu Güner Gültekin
et al.

Abstract: PurposeAritificial intelligence (AI)-focused enterprises purpose to provide value-creating and differentiated products and services using innovative technologies. For this reason, it is aimed to examine the effects of value creation, intellectual property and organizational creativity variables to make evaluations to increase the success of such enterprises.Design/methodology/approachRandom sampling method was used in the research. The population of the research consists of AI-oriented enterprises in technopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Proposed relations between these variables were confirmed in a study by Pinarbasi et al. (2024) of high-tech enterprises operating in technoparks within the Turkish province of Istanbul.…”
Section: Study Evidence From Turkeymentioning
confidence: 67%
“…Proposed relations between these variables were confirmed in a study by Pinarbasi et al. (2024) of high-tech enterprises operating in technoparks within the Turkish province of Istanbul.…”
Section: Study Evidence From Turkeymentioning
confidence: 67%
“…This consideration of the impact of AI and intellectual property has formed the basis for the work done by Pinarbasi et al (2024), wherein they have considered the impact of creativity on AI-focused firms in the technology industry of Türkiye. They have identified that, in order to gain and sustain a competitive advantage in both the local and global technology markets, these firms need to harness the organizational creativity which is associated with research and development as enhanced by AI.…”
Section: Creative Advantagementioning
confidence: 99%
“…This can mean unlocking the time and potential of employees to be creative and innovate whilst harnessing AI to fulfil more menial and process-heavy roles, thereby improving organizational efficiency at the same time as boosting original creativity. The main driver to implementing this, according to Pinarbasi et al (2024) is the recognition and acceptance of intellectual property, which offers protection and ringfenced returns for creativity. The combination of these elements can therefore be seen to generate considerable competitive advantage.…”
Section: Creative Advantagementioning
confidence: 99%